2022
DOI: 10.1021/acsaenm.2c00111
|View full text |Cite
|
Sign up to set email alerts
|

Protease Immobilization in Solution-Blown Poly(ethylene oxide) Nanofibrous Nonwoven Webs

Abstract: Enzyme-functionalized solution-blown nonwoven (EFSBN) fibers were produced by a single-step solution blow spinning method that utilizes high-velocity gas to simultaneously extrude the codissolved polymer−solvent−enzyme spinning solution and evaporate solvent at mild conditions to form a nanofibrous web with preserved enzyme activity. A broad concentration range of 0.6−7.4 wt % protein of subtilisin A protease from Bacillus licheniformis was successfully entrapped by poly(ethylene oxide) (PEO) during solution b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 70 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…Tyler et al demonstrated the use of triatomic Bi 3 + as the primary ion and a maximum autocorrelation factors (MAF) image-processing method for generating a clear contrast (boundaries confirmed by fluorescence microscopy) between two similar proteins (human serum albumin versus bovine serum albumin) and two very different proteins (human serum albumin versus hemoglobin) immobilized on non-flat polystyrene micro-bead surfaces [ 269 ]. This demonstration of the technique on complex-shaped surfaces instead of regular flat substrates, such as silicon wafers, indicates that TOF-SIMS can also be applied to study the distribution of enzymes immobilized on fibrous supports, as was carried out with protease incorporated in poly(ethyleneoxide) solution, blown, nonwoven webs [ 270 ]. The technical parameters of different surface characterization techniques are compared in Table 7 .…”
Section: Characterization Of Enzyme-immobilized Fibrous Materialsmentioning
confidence: 99%
“…Tyler et al demonstrated the use of triatomic Bi 3 + as the primary ion and a maximum autocorrelation factors (MAF) image-processing method for generating a clear contrast (boundaries confirmed by fluorescence microscopy) between two similar proteins (human serum albumin versus bovine serum albumin) and two very different proteins (human serum albumin versus hemoglobin) immobilized on non-flat polystyrene micro-bead surfaces [ 269 ]. This demonstration of the technique on complex-shaped surfaces instead of regular flat substrates, such as silicon wafers, indicates that TOF-SIMS can also be applied to study the distribution of enzymes immobilized on fibrous supports, as was carried out with protease incorporated in poly(ethyleneoxide) solution, blown, nonwoven webs [ 270 ]. The technical parameters of different surface characterization techniques are compared in Table 7 .…”
Section: Characterization Of Enzyme-immobilized Fibrous Materialsmentioning
confidence: 99%
“…Solution-blown nonwoven webs were produced using the same instrument and method described in our previous work [27]. PCL-based spinning solutions were prepared by dissolving PCL pellets (1.5 g) in AOT surfactant-loaded (1 mg AOT/mL solvent) chloroform (10 mL) with continuous (2 h) stirring (250 rpm).…”
Section: Sbn-pcl and Efsbn-pcl Web Productionmentioning
confidence: 99%
“…The protein (enzyme) content in EFSBN-PCL was determined by modifying Lowry assay method described in our previous work [27]. A Thermo Scientific Pierc Rapid Gold Bicinchoninic Acid (BCA) Protein Assay Kit was used for this analy where two molecules of BCA combine with one cuprous ion to form an orange-gold lution with an absorbance intensity at 480 nm that correlates to protein concentrat EFSBN-PCL webs were first incubated at 40 °C in tris buffer (pH 8.0, 0.1 M) for 120 m to degrade the webs entirely.…”
Section: Protein Content and Immobilization Yield Of Efsbn-pclmentioning
confidence: 99%
See 1 more Smart Citation